Chapter Un réseau corse entre l’Afrique du Nord et l’Europe. Commerce maritime, institutions et enrichissement au tournant des XVIe et XVIIe siècles - Calafat, Guillaume (Atti delle «Settimane di Studi» e altri Convegni, 2019)
This article describes the activity of a network of Corsican merchants and sailors active in the Western Mediterranean between the sixteenth and the seventeenth century, in particular in Tunis, Marseille, Leghorn and the areas of Corsica under Genoa’s rule. Based on early-seventeenth-century factums and memorials, and notary deeds and documents from the archives of the Record’s Office of the French Consulate in Tunis, this essay describes how several families of Corsican merchants – some naturalised French in Marseille, some converted to Islam in Tunis – were part of the political and economic elites of the Mediterranean area.